Toripalimab plus cetuximab combined with radiotherapy in a locally advanced platinum-based chemotherapy-insensitive nasopharyngeal carcinoma patient: a case report - Piao, Ying; Yang, Yao; Wu, Shihai; Han, Ling (Frontiers in Oncology, 2024)
Background Locoregionally advanced nasopharyngeal carcinoma (NPC) is an epithelial malignancy that primarily occurs in East and Southeast Asia, and it is associated with relatively poor overall survival (OS). Currently, there is no reliably effective standard treatment for NPC that progresses after first-line therapy with platinum-based chemotherapy. Case report A 55-year-old woman diagnosed with stage IVa NPC received two cycles of platinum-based chemotherapy but encountered an increase in the size of cervical lymph nodes and suffered from adverse events. The patient was then switched to toripalimab plus cetuximab combined with radical radiotherapy and had a complete clinical response within 2 months following the completion of radiotherapy without severe treatment-related adverse events. Conclusion This case report showed that toripalimab plus cetuximab combined with radiotherapy for the treatment of patients with locoregionally advanced nasopharyngeal carcinoma may result in a fast and durable response with a manageable safety profile.